HEAVY METAL IONS DETECTION USING GRAPHENE FET DNA SENSOR - Abdullah, Nurul Naiemah (2017)
Heavy metal ion is defined as a metallic and toxic chemical substances that has very high density. The example of heavy metal ions are cadmium, mercury, arsenic, lead and chromium. They are very harmful and can cause many health issues towards people as they are very easy to enter our body via water, food and air. Although in very low-dose exposure, they can cause serious health complication. Thus, the prevention stage like detection of ions is required in order to prevent them from penetrate into human body.